Building bridges a comparative analysis of outreach programs of public city libraries in the National Capital Region - Valila, Nadeshya T. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2019)
Public libraries have vital roles in the provision of necessary knowledge to satisfy the information needs of the community they are serving. They are also bound to develop the literacy of the people in their community by innovating programs that will attract the people to use the library services. This include conducting outreach programs, to further ensure that all sectors are equally tapped and being provided opportunities and services by the public libraries. This study aimed to identify the existing outreach programs. That are being conducted by different public city libraries in the National Capital Region. The data gathered were compared and analyzed to ferret out the best practices, which can, later on, be adopted by other institutions without outreach programs.
In the Philippines, very little study has been done that tackle how outreach programs help in developing a reading society. Because of this, the researcher employed an exploratory research design to further identify other aspects affecting the public libraries in conducting outreach programs. A semi-structured interview was utilized to capture elements which may not be quantified.
The study showed that out of 15 public city libraries in the NCR, only six have outreach programs. The outreach programs that were identified primarily served the students, out-of-school youth, senior citizens, inmates, people deprived of liberty, children in conflict with the laws, and non-library users in general. Different approaches are being done by different public city libraries depending on the information needs of their patrons. The challenges that were identified by the librarians and officers-in-charge during the interview include the lack of support from the local government due to politics, budgets constraints, lack of skilled staff, failed partnerships consistency and sustainability of the programs.
Thesis (Bachelor of Library and Information Science)